Diffuse Sclerosis and its Treatments - Hotamov Bekzod Farhodovich (Genius Journals, 2022)
This article brings information about diffuse sclerosis and its modern and new treatments, which will be studied in the Department of neurapatology
Keywords: Nervous system; myelitis; marrow; neurology